2016
DOI: 10.1007/s00520-016-3363-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings of home bortezomib injection in patients with multiple myeloma treated by a combination care in Outpatient Hospital and Hospital care at Home

Abstract: At home injectable chemotherapy for patients receiving treatment for hematological diseases is still in debate. Given the expense of new innovative medicines, at home treatment has been proposed as a suitable option for improving patient quality of life and decreasing treatment costs. We decided to assess the cost of bortezomib administration in France among multiple myeloma patients from an economic standpoint. Patients in this study were treated within a regional hematological network combining outpatient ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…For example, treatment with a novel agent or regimen in the real-world setting may be associated with substantial patient time and economic burden 91 , 92 , including direct and indirect costs associated with medications and attending regular clinic visits. The burden of treatment, such as the route of administration and travel to the treatment center 10 , 93 , may not be captured by standard clinical trial endpoints but may substantially affect the feasibility of long-term treatment in the real-world setting as patients may succumb to treatment fatigue outside of the ‘motivating’ environment of clinical trial participation. Differences in adherence to treatment between a stringently monitored clinical trial setting and routine care may thus impact the generalizability of trial results to the real world.…”
Section: Understanding Disparities Between Different Clinical Trials mentioning
confidence: 99%
“…For example, treatment with a novel agent or regimen in the real-world setting may be associated with substantial patient time and economic burden 91 , 92 , including direct and indirect costs associated with medications and attending regular clinic visits. The burden of treatment, such as the route of administration and travel to the treatment center 10 , 93 , may not be captured by standard clinical trial endpoints but may substantially affect the feasibility of long-term treatment in the real-world setting as patients may succumb to treatment fatigue outside of the ‘motivating’ environment of clinical trial participation. Differences in adherence to treatment between a stringently monitored clinical trial setting and routine care may thus impact the generalizability of trial results to the real world.…”
Section: Understanding Disparities Between Different Clinical Trials mentioning
confidence: 99%
“…To our knowledge, there is limited evidence on healthcare and societal costs of home-based SC administration of oncology drugs. A recent systematic review [10] identified two studies [19,20] a For home-based administration, costs for the preparation of the injection related to the time of healthcare professionals and usage of consumables were included in costs for ready to use trastuzumab injection. b Costs of adminstrative staff (planner) in the hospital setting were included in the overhead costs (thus not in the active time of healthcare professionals).…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of data regarding resource utilization is limited due to differences in clinical practice and healthcare systems between the different countries participating in eVOBS. Although patients appeared to be managed predominantly in the outpatient setting in eVOBs, the subsequent introduction of subcutaneous bortezomib has enabled home administration which is cost‐saving as well as more cost‐effective and is preferred by patients . Furthermore, the recent advent of all‐oral regimens such as lenalidomide‐dexamethasone‐ixazomib has also increased patient convenience and the potential for home‐based management.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients appeared to be managed predominantly in the outpatient setting in eVOBs, the subsequent introduction of subcutaneous bortezomib has enabled home administration which is cost-saving as well as more cost-effective and is preferred by patients. [38][39][40] Furthermore, the recent advent of all-oral regimens such as lenalidomidedexamethasone-ixazomib 41 has also increased patient convenience and the potential for home-based management.…”
Section: Discussionmentioning
confidence: 99%